Keseimbangan Bandwidth Dengan Menggunakan Dua ISP Melalui Metode Nth Load Balancing Berbasiskan Mikrotik - Toni Sukendar (Universitas Bina Sarana Informatika, 2017)
Along with the increasing need to use existing resources in the development of computer network technology has led to the emergence of the network itself. Availability of resources will be inversely proportional to the level of need are now demanding networking technologies floated a new technique that can resolve the issue. Load balancing is a technique that can harness routing multiple resources to be used simultaneously. However, there are various methods that can also be used, including methods of NTH, PCC load balancing and Fail Over. This study discusses the NTH Load Balancing Methods In balancing the bandwidth in order to make the resources of the Internet to be optimal.Keywor:- load Balancing, Nth, Bandwidth